Association between school learning models and psychological and social health visits to the emergency room - Kit Knier; Aliza Weinman; Aidan Mullan; Meghan Cain; Sara Hevesi; Venkatesh R. Bellamkonda (Journal of the American College of Emergency Physicians Open)
Abstract Objectives We aimed to assess the impact of in‐person and distance school learning models on children's visits to the emergency department (ED) for psychological or social (“psychosocial”) complaints. Methods We analyzed presentations to one emergency department in a mid‐sized Midwestern city. We used the public school system schedule to determine in‐person and distance learning periods by the grade level. We calculated the incidence of visits to the emergency department during academic years 2018–2019, 2019–2020, and 2020–2021, with particular attention to the time after March 13, 2020, which was the pandemic period. We compared the incidence of visits during in‐person versus distance learning school models. Results A total of 7181 visits occurred during the academic years studied, 17.1% due to psychosocial complaints. The incidence of psychosocial visits to the ED was lower during distance learning than during the pandemic in‐person learning period (given per 1000 student years: 20.5 vs. 24.1, p = 0.14). This difference was statistically significant among middle schoolers (23.3 vs. 46.6, p < 0.001). While not statistically significant, the difference among high schoolers was pragmatically relevant (38.2 vs. 49.3, p = 0.086). Conclusions Distance learning was associated with a decrease in the incidence of psychosocial visits to the emergency department relative to in‐person learning. Future investigation is required to verify results and better understand any causative relationships.